Urban–rural integration drives regional economic growth in Chongqing, Western China. Issue 1 (2nd January 2016) - Liu, Weidong; Dunford, Michael; Song, Zhouying; Chen, Mingxing
ABSTRACT: The recent experience of rapid economic growth in Chongqing Municipality in Southwest China shows that rural–urban integration can drive regional growth. In Chongqing rural–urban migration, rural–urban land conversion, infrastructure investment, agricultural restructuring, rural development and employment generation drive growth. These generic processes are profoundly shaped by the policy-driven investment dynamics and the specificity of the Chinese social model. Chinese specificity is reflected in Hukou reform, urban and rural rights, the Annual Land Use Quota system, the di piao, public assets and the local government finance vehicles.